Impact of Locus of Control on Depression of Elderly In Punjab, Pakistan: The Moderating Role of Religosity;An empirical evidence - Khurram, Fatima; Mat Saad, Zarina; Mahamood, Yahaya (2017)
The current research was intended to see the impact of locus of control on the depression of elderly in Punjab, Pakistan and the role of religiosity as a moderator.The sample of the present study consisted of 800 older individuals of Pakistan.They were further equally divided into males and females 400 each.Correspondingly, The data on elderly population was chosen from the different areas of Punjab, Pakistan.To measure the level of depression short form of geriatric depression scale was used.To, measure the level of locus of control Levenson Multidimensional locus of control scale was used.The findings of the research describe that there is a positive relation between the level of locus of control and depression of elderly.In contrast, when religiosity as a moderator is introduced then the positive relation becomes negative.Which means the religiosity have a negative impact on depression. The more the person religious, he/she has a low chance of developing depression in its later age.